Wednesday

April 16, 2014

April 16, 2014

Posted by **Sherina** on Friday, October 5, 2012 at 1:37pm.

- Algebra 2 -
**Reiny**, Friday, October 5, 2012 at 2:10pmlet 2b - 1= x

2b = x+1

b = (x+1)/2

then for

f(2b-1) = 6b = 2

f(x) = 6(x+1)/2 + 2

=3(x+1) + 2

= 3x + 5

f(x) = 3x + 5

check by replacing x with 2b-1

f(2b-1) = 3(2b-1) +5 = 6b -3+5

= 6b + 2 , as given

**Related Questions**

Math - Find the HCF 1) 7x and 9 : nothing 2) x^2(x-4) and x(x-4) : its (x-4)? 3...

Algebra 2 - Find f(x), if f(2b-1)=6b+2

Tirginometry - the expression 4ab(square root of)2b-3a(square root of)18b^3+7ab(...

Algebra 1 - Find Each Sum Or Difference. Its addition. 3a+2b - 7c -4a+6b+9c -3a...

math,algebra - can someone help me i've tried different numbers but i can come ...

math help - If 3ab=6, what is the value of a in terms of b? a. 2 b. 2/b c. 2b^2 ...

algebra 1 - 7a+[4a-6b-(8a+2b)] ok so you would get this 7a+[4a-6b-8a-2b]<--- ...

algebra - 1 Solve the set of linear equations by the matrix method : a+3b+2c=3...

Math(Please Check My Work.) - 3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this ...

algebra - LCM of 15 c^2b^6, 5c^6b^4, 6c^7b^3